TruCluster server handbook - Fafrak, Scott (Amsterdam ; Boston : Digital Press, 2003)
The TruCluster Server Handbook authoritatively details how to plan, design, install, configure, and administer a cluster of Tru64 UNIX systems. The book explains how to configure and optimize hardware underlying a TruCluster server, including storage servers so critical to running a high-end cluster operation. This book provides best practices and techniques drawn from the authors' extensive experiences in the field with systems designers, systems managers, developers, and users. The authors include a former Tru64 UNIX Technical Group Leader with HP's Consulting Division and a top industry figure, and two former TruCluster Server Team Leaders with the Customer Support Center. Learn to install TruCluster Server from the ground up Get the most out of your cluster environment with the authors' practical tips and tricks Attain availability, scalability, and simplified manageability in your IT systems operation.
Part I: Introduction; Tru64 UNIX and TruCluster Overview -- Part II: Design and Configuration of a Tru64 UNIX Cluster: Designing a Cluster; Technology Considerations for a Cluster; Cluster Configuration Planning -- Part III: Installing and Configuring the Tru64 Operating System: Installing Tru64 UNIX; Configuring Tru64 UNIX -- Part IV: Cluster Hooks: File System Hierarchy, Context Dependent; Symbolic Links, Process IDs; Device Naming and Hardware Management; The Event Manager; Network Interface Failure Finder, NetRAIN, and Link Aggregation -- Part V: Creating a Cluster: Planning the Cluster Implementation; Creating and Configuring a Single Node Cluster; Cluster Installation Verification; Part VI: Adding and Removing Cluster Members: Planning for Adding a New Cluster Member; Adding and Configuring the New Cluster Member/Deleting a Cluster Member; Verifying the Configuration of a New Cluster Member; Cluster Hooks; Part VII: Cluster Subsystems: Devices and File Systems; Communications -- Part VIII: Cluster System Administration: System, Network, and Cluster Administration Tasks; Maintenance and Recovery -- Part IX: Application Deployment in a Cluster: Cluster Application Availability; Application Deployment Examples -- Part X: Upgrading and Patching a Cluster: Performing a Rolling Patch or Upgrade; Considerations for Migrating to TruCluster Server -- Part XI: Appendices: Programming APIs; Resources; Glossary.
Includes bibliographical references and index.
Keywords: Parallel processing (Electronic computers); Electronic data processing -- Distributed processing; Client/server computing; Electronic books